Development Media Teaching of Physics by LMS Moodle with Modellus to Improve Students' Analysis Ability - Hana Wahyuni; Ashari Ashari; Yusro Alhakim (Berkala Ilmiah Pendidikan Fisika, 2023)
This development media teaching of physics by Moodle basic Modellus with wave equation material aimed to improve the student's ability in analysis. In this research, the researcher developed ADDIE models: analysis, design, development, implementation, and evaluation. The research took place in SMA Negeri 1 Petanahan Kebumen with the subject researcher with limited testing to five students and, in the Implementation step eighteen students. The data analysis the researcher used is a validation sheet, questionnaire, observation technique, and the result of students' tests. Based on the research, we can conclude that: (1) the validation result from the expert validator is 3.10, from the material expert is 3.27, from the media expert gained a good category, which means valid, 2) the media physics learning process LMS Moodle basic Modellus practical because it works in limited trials and great trials, and received a positive response, and 3) the analysis test result there is an increase learning progress with N-gain as 0.70, it means high category and its effective. Similarly, learning physics by LMS Moodle with Modellus on this researcher is valid, practical, and effective. Furthermore, it works to improve the student's ability in analysis.